Sequential fullerenylation of bis-malonates-efficient access to oligoclusters with different fullerene building blocks - Wasserthal, Lennard; Kratzer, Andreas; Hirsch, Andreas (European Journal of Organic Chemistry, 2013)
A method for the sequential fullerenylation of bis-malonates with parent C and C-symmetric pentakis-adducts is reported. This approach relies on the finding that (a) chloromalonates can be used for the nucleophilic cyclopropanation of [6,6] double bonds of C, and (b) chloromalonates, in contrast to bromomalonates, do not undergo base-catalyzed halogen exchange reactions. For the proof of concept, we synthesized a heptafullerene by using a divergent approach based on a fullerene hexakis-adduct with six bis-malonate addends in octahedral positions, each of which is suitable for an additional cyclopropanation of a fullerene building block. A sequence for the selective fullerenylation of bis-malonates with C and its exohedral C-symmetric pentakis-adducts has been developed. This method enables the straightforward synthesis of highly functional fullerene derivatives such as the heptafullerene 1. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.